Erotic fantasy, spirituality and Song of Songs - Van der Merwe, Dirk 1952- (2017)
Fantasy plays an essential role in sexual activities. This article investigates (erotic) fantasy from a literary text perspective according to Song of Songs in the Christian Bible. The Song, according to many commentaries, starts with a reference to sex in Canticle 1:2, Let him kiss me with the kisses of his mouth! For your love is better than wine'. Although the word sex is not mentioned in the Song, it is referred to and implied a number of times in the deep structure of the text. The fantasies of this most beautiful woman (beauty, a secondary motif in the Song that is complementary to the main theme of love) are part of the rhetoric of the poet (probably a woman) to convince the reader about the enjoyment and beauty of erotic love. These could most likely stimulate erotic fantasies when reading the text. Part of the poet's rhetoric is the way in which she describes this most beautiful woman and her most attractive lover using metaphors, allusions, symbols and similes to evoke all sorts of imaginations and fantasies in the mind of the reader to complement the erotic fantasies of the reader. The investigation of the composition and lived experiences' (spiritualities) of erotic fantasies is approached from the perceptions of how the entanglement of the reader in the text augments fantasies, how the dynamic interaction between the text of Song of Songs and the reader involves the reader in the fantasies and spiritualities of the protagonists and the poet, how the lived experiences of the composed images and erotic fantasies in the text of the Song grip and involve the reader in the text and finally how the use or application of human senses in fantasies can intensify the lived experiences of fantasies. This research points out how God's love and concern for his creatures are present as revealed in the relationship between two lovers. His love and concern are clearly visible in the enjoyment and pleasure given by God to humans in his creation which the lovers find in each other.Intradisciplinary and/or interdisciplinary implications: This research challenges the traditional discourse about sexuality for an enrichment of it. In the article the disciplines of theology, physiology, psychology and spirituality unite to include the entire person in sexual activities. The potential results would end up in a greater enjoyment of making love.